Red phosphorus / montmorillonite photoresponse composite material as well as preparation method and application thereof
By preparing red phosphorus/montmorillonite photoresponsive composite materials, the separation and transmission of photogenerated carriers are enhanced by the layered structure of montmorillonite and the separation and transmission of photogenerated carriers are solved, and efficient photocatalytic degradation and antibacterial effects are achieved in the visible light range.
Patent Information
- Application Number
- CN202510172644.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-02-17
AI Technical Summary
Traditional semiconductor photocatalysts such as titanium dioxide and zinc oxide can only be activated by ultraviolet light, resulting in low photocatalytic efficiency. As visible semiconductor materials, the rapid recombination of red phosphorus photogenerated carriers limits its application.
By stirring, separating and vacuum drying of red phosphorus and montmorillonite in a specific solvent, a red phosphorus/montmorillonite photoresponsive composite material is prepared. The layered structure of montmorillonite and good ion exchangeability form P-O-Si chemical bonds with red phosphorus, enhancing the separation and transmission efficiency of photogenerated carriers.
The composite material significantly improves the photocatalytic degradation of orange-yellow II and antibacterial properties in the wavelength range of 420-780nm, overcomes the disadvantages of rapid recombination of red phosphorescence and holes, and improves photocatalytic activity and pollutant removal efficiency.
Smart Images

Figure CN119909768A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalysts, and in particular to a red phosphorus / montmorillonite light-responsive composite material and a preparation method and application thereof. Background Art
[0002] Semiconductor photocatalysis technology has been developed as an alternative way of water purification due to its advantages such as strong disinfection ability, energy saving and environmental protection, no toxic byproducts and self-purification. When semiconductor materials are stimulated by light, electron holes can be generated, and further reactive oxygen species (ROS) can be generated in the presence of oxygen, which has been proven to be effective in the photodegradation of organic pollutants and inactivation of bacteria.
[0003] Traditional photocatalysts such as titanium dioxide (TiO) and zinc oxide (ZnO) can only be activated by ultraviolet light, which accounts for 4% of the solar spectrum, resulting in unsatisfactory photocatalytic efficiency. To this end, researchers are committed to developing new photocatalysts that can be activated by visible light. Red phosphorus (RP) is a low-cost, chemically stable and biocompatible visible light semiconductor material. However, the rapid recombination of its photogenerated carriers restricts its further use. Summary of the invention
[0004] The purpose of the present invention is to provide a red phosphorus / montmorillonite light-responsive composite material and a preparation method and application thereof in view of the above-mentioned deficiencies in the prior art.
[0005] The first purpose of the present invention is to provide a method for preparing a red phosphorus / montmorillonite light-responsive composite material, wherein the red phosphorus is impurity-removed and ultrasonically peeled to obtain flaky red phosphorus, and the flaky red phosphorus and montmorillonite are stirred, separated, and vacuum-dried in a first solvent to obtain the red phosphorus / montmorillonite light-responsive composite material.
[0006] Furthermore, the mass ratio of the flaky red phosphorus to the montmorillonite is 0.1-0.9:1.
[0007] Furthermore, the montmorillonite is ground.
[0008] Furthermore, the montmorillonite is placed in a ball mill and fully ground for 2-5 hours.
[0009] Furthermore, the first solvent is one or more of N-methylpyrrolidone, water, or ethanol; and the stirring time is 1-4h.
[0010] Furthermore, the specific operation of removing impurities is: putting red phosphorus into water and ultrasonically dispersing it to obtain a red phosphorus suspension, subjecting it to a hydrothermal reaction, naturally cooling, washing, centrifuging, and vacuum drying; the concentration of the red phosphorus suspension is 0.08 g / mL, the hydrothermal reaction temperature is 180-200° C., and then vacuum drying is performed at 65° C. for 12-24 hours.
[0011] Furthermore, the specific operation of ultrasonic stripping is: ultrasonically dispersing the removed red phosphorus in a second solvent, then washing with ethanol, centrifuging, and vacuum drying; the second solvent is one or more of N-methylpyrrolidone, water, or ethanol.
[0012] Furthermore, the mass volume ratio of the red phosphorus after impurity removal to the second solvent is 1:1 g / L; the ultrasonic power is 800 W, and the time is 2-4 h.
[0013] Furthermore, the centrifugal speed is 8000-12000 rpm for 5-20 min, and then the vacuum drying is performed at 60-70° C. for 12-24 h.
[0014] The second object of the present invention is to provide a red phosphorus / montmorillonite light-responsive composite material prepared by the above-mentioned preparation method.
[0015] The third object of the present invention is to provide a red phosphorus / montmorillonite light-responsive composite material as described above for use as a photocatalyst for photocatalytic degradation of Orange II and antibacterial properties at a wavelength of 420-780 nm.
[0016] In the responsive composite material prepared by the present invention, montmorillonite is a clay mineral with a special layered structure and a large specific surface area, and it has good ion exchange and adsorption properties; the layered structure of montmorillonite can provide a stable support framework for red phosphorus, effectively inhibiting the recombination of red phosphorus photogenerated carriers, and the combination of montmorillonite and red phosphorus through the formation of PO-Si chemical bonds enhances the separation and transmission efficiency of photogenerated carriers, and the construction of the composite material overcomes the shortcomings of fast recombination of red phosphorus photogenerated electrons and photogenerated holes, improves the photocatalytic activity, and improves the photocatalytic removal of pollutants and antibacterial performance of the composite material. At the same time, montmorillonite can also enrich pollutants and bacteria in the surrounding environment with its strong adsorption capacity, making pollutants and bacteria more accessible to red phosphorus photocatalysts, thereby improving the efficiency of photocatalytic reactions.
[0017] The responsive composite material prepared by the invention has good cycle stability.
[0018] The preparation method of the present invention uses commonly used chemical reagents, which are widely available, cheap and easy to obtain; the reaction equipment is simple, the reaction conditions are mild, and only the hydrothermal process is performed, the synthesis temperature is low, and the preparation steps are simple; BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The performance diagram of photocatalytic removal of Orange II by the products of Examples 1-2 and Comparative Examples 1-3 of the present invention;
[0020] Figure 2 The products of Example 1 and Comparative Examples 1 and 2 of the present invention are visible light photocatalytic antibacterial;
[0021] Figure 3 It is the X-ray diffraction pattern of the products of Examples 1-2 and Comparative Examples 1-3 of the present invention;
[0022] Figure 4 It is the X-ray photoelectron spectrum of the products of Examples 1-2 and Comparative Example 1 of the present invention;
[0023] Figure 5 It is the Fourier transform infrared spectra of the products of Examples 1-2 and Comparative Examples 1-3 of the present invention;
[0024] Figure 6 It is the transient fluorescence spectra of the products of Examples 1-2 and Comparative Example 1 of the present invention;
[0025] Figure 7 The scanning electron microscope images and EDX mapping images of the products of Example 2 and Comparative Example 1 of the present invention are shown;
[0026] Figure 8 The XRD diagram of the product prepared in Example 2 before and after degradation of Orange 2 after 5 cycles;
[0027] Fig. 9 This is a graph showing the degradation rate of the product prepared in Example 2 after five cycles of degradation of Orange 2. DETAILED DESCRIPTION
[0028] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.
[0029] It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial channels unless otherwise specified.
[0030] Embodiment 1:
[0031] This example prepares a red phosphorus / montmorillonite light-responsive composite material, and the specific preparation steps are as follows:
[0032] (1) Add 5 g of red phosphorus to 65 mL of deionized water, ultrasonicate for 30 min, transfer to a reactor, incubate at 200 °C for 24 h, cool to room temperature, wash with deionized water, centrifuge, and vacuum dry to obtain product A;
[0033] (2) 0.22 g of product A was added to 220 mL of NMP and ultrasonicated at 800 W for 4 h. The mixture was centrifuged at 12,000 rpm for 20 min and then vacuum dried at 65 °C for 24 h to obtain product B.
[0034] (3) The mass ratio of B to the directly purchased montmorillonite is 0.1-0.9, the stirring time is 1 hour, and then vacuum drying is performed at 65° C. for 24 hours to obtain a red phosphorus / montmorillonite photoresponsive composite material, which is marked as RP / MMT;
[0035] Embodiment 2:
[0036] This example prepares a red phosphorus / montmorillonite light-responsive composite material, and the specific preparation steps are as follows:
[0037] (1) Add 5 g of red phosphorus to 65 mL of deionized water, ultrasonicate for 30 min, transfer to a reactor, incubate at 200 °C for 24 h, cool to room temperature, wash with deionized water, centrifuge, and vacuum dry to obtain product A;
[0038] (2) Add 0.22 g of product A to 220 mL of NMP and ultrasonicate at 800 W for 4 h; centrifuge at 12,000 rpm for 20 min and then vacuum dry at 65 °C for 24 h to obtain product B;
[0039] (3) Place the montmorillonite in a ball mill and grind it thoroughly for 4 hours to obtain product C.
[0040] (4) The mass ratio of product B and product C is 0.9, dispersed in an ethanol solution, stirred for 1 hour, and then vacuum dried at 65° C. for 24 hours to obtain a red phosphorus / montmorillonite photoresponsive composite material, labeled as RP / eMMT;
[0041] Comparative Example 1: Red Phosphorus Catalyst
[0042] 5g of red phosphorus was added to 65mL of deionized water, ultrasonicated for 30min, transferred to a reactor, reacted at 200℃ for 24h, cooled to room temperature, washed with deionized water, centrifuged, and vacuum dried to obtain product A. 0.22g of product A was added to 220mL of NMP and ultrasonicated at 800W for 4h; centrifuged at 12000rpm for 20min, and then vacuum dried at 65℃ for 24h, marked as RP.
[0043] Comparative Example 2: Montmorillonite
[0044] Montmorillonite purchased directly is marked as MMT.
[0045] Comparative Example 3: Modified montmorillonite
[0046] The directly purchased montmorillonite was placed in a ball mill and ground for 4 h and marked as eMMT.
[0047] Experimental results show that the photocatalytic removal of Orange II by the red phosphorus / montmorillonite light-responsive composite material prepared in Example 2 of the present invention, the red phosphorus catalyst (RP) obtained in Comparative Example 1, and the modified montmorillonite (eMMT) in Comparative Example 3 were evaluated. The photocatalytic antibacterial performance of the red phosphorus / montmorillonite light-responsive composite material prepared in Example 1 of the present invention, the red phosphorus catalyst (RP) obtained in Comparative Example 1, and the montmorillonite (MMT) in Comparative Example 2 were evaluated.
[0048] The specific steps are:
[0049] Figure 1 The performance diagram of photocatalytic removal of orange II by Examples 1 and 2 of the present invention and Comparative Examples 1-3 is shown. It can be seen that the performance of photocatalytic removal of orange II by Example 2 of the present invention is the best.
[0050] Figure 2 The photocatalytic antibacterial performance diagram of Example 1 of the present invention, Comparative Example 1 and Comparative Example 2. It can be seen that the photocatalytic antibacterial performance of Example 1 of the present invention is higher than that of Comparative Examples 1 and 2.
[0051] Figure 3 The X-ray diffraction spectra of Examples 1-2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention are compared with single red phosphorus and single montmorillonite. It can be seen that Examples 1-2 of the present invention contain two substances, red phosphorus and montmorillonite, and no other impurities are present.
[0052] Figure 4 The X-ray photoelectron energy spectra of Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention show that the O1s spectrum of single red phosphorus mainly shows the peaks of POP and P=O bonds. In comparison, the characteristic peak of Si-O in the PO-Si bond appears in the O1s spectrum of RP / MMT and RP / eMMT, which confirms that chemical bonding occurs after the montmorillonite and red phosphorus are composited, and this bonding has an important influence on the performance of the composite material.
[0053] Figure 5 The Fourier transform infrared spectra of Examples 1-2, Comparative Examples 1, 2 and 3 of the present invention show that RP / MMT and RP / eMMT show characteristic absorption peaks different from those of single red phosphorus and single montmorillonite. At about 1100 cm-1, there is an obvious POP absorption peak in the curve of red phosphorus, but in the curves of RP / MMT and RP / eMMT, the POP absorption peak at this position gradually disappears. At the same time, the absorption peak of the PO bond gradually increases and gradually blue-shifts (towards the direction of increasing wave number). This phenomenon indicates that with the compounding of montmorillonite and red phosphorus, especially in RP / eMMT, the formed PO-Si bond becomes more and more stable.
[0054] Figure 6The transient fluorescence spectra of Examples 1-2 and Comparative Example 1 of the present invention are shown in Figure 1. Transient fluorescence spectroscopy is an effective means to study carrier transfer and separation in semiconductor catalysts. The fluorescence intensity of RP decays relatively quickly, and its average lifetime of photogenerated carriers is only 13.6ns, indicating that carrier recombination is relatively fast in pure red phosphorus and separation is relatively difficult. The fluorescence lifetime of the red phosphorus / montmorillonite composite material is lower than that of pure red phosphorus, indicating that the PO-Si bond builds a more efficient transmission channel for photogenerated electrons, allowing photogenerated electrons to be quickly transferred from the surface of red phosphorus to montmorillonite, effectively inhibiting the recombination of photogenerated electrons and holes, thereby significantly improving the photocatalytic removal of orange II and antibacterial performance of red phosphorus.
[0055] Figure 7 The transmission electron microscope images and EDX mapping images of Example 2 and Comparative Example 1 of the present invention show that the layered montmorillonite and the lamellar red phosphorus have been successfully composited together and are evenly distributed in the composite material. From the EDXmapping distribution image of the composited elements, the distribution of Si, Al, O, P and other elements can be clearly observed.
[0056] Figure 8 The XRD diagram of the product prepared in Example 2 before and after the degradation of Orange 2 after 5 cycles. The overall shape and trend of the curves before and after the reaction are similar, and there are no impurity peaks, indicating that the material has good cyclic stability;
[0057] Fig. 9 The degradation rate of Orange 2 after 5 cycles of the product prepared in Example 2 is shown in the figure. As can be seen from the figure, the degradation rate of Orange 2 after 5 cycles is still maintained at a relatively high level, indicating that the material has good cyclic stability.
[0058] The present invention uses a variety of characterization methods such as XRD, SEM, TEM, XPS, etc. to characterize its crystal structure, morphological characteristics, and light absorption performance, and proves that red phosphorus forms a chemical bond with montmorillonite to form a composite material, which is of great significance for overcoming the disadvantage of fast recombination of photogenerated electrons and photogenerated vacancies in RP. The formation of a heterojunction overcomes the disadvantage of fast recombination of photogenerated electrons and photogenerated holes in red phosphorus and improves the photocatalytic activity.
[0059] In summary, the present invention provides a red phosphorus / montmorillonite light-responsive composite material, a preparation method and an application thereof, wherein montmorillonite accelerates the transport process of photogenerated carriers of red phosphorus, photogenerated electrons and holes are effectively separated, and the photocatalytic removal of orange-yellow II and antibacterial performance of red phosphorus are enhanced. The red phosphorus / montmorillonite light-responsive composite material provided by the present invention has good photocatalytic performance, and the preparation method is simple in process, mild in conditions, low in cost, and can achieve large-scale production.
[0060] For matters not mentioned above, the prior art applies.
[0061] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a red phosphorus / montmorillonite light-responsive composite material, characterized in that: The red phosphorus is impurity-removed and ultrasonically peeled to obtain flaky red phosphorus, and the flaky red phosphorus and montmorillonite are stirred, separated and vacuum-dried in a first solvent to obtain a red phosphorus / montmorillonite light-responsive composite material.
2. The preparation method according to claim 1, characterized in that: The mass ratio of flaky red phosphorus to montmorillonite is 0.1-0.9:
1.
3. The preparation method according to claim 1, characterized in that: Montmorillonite is ground.
4. The preparation method according to claim 3, characterized in that: Place the montmorillonite in a ball mill and grind it thoroughly for 2-5 hours.
5. The preparation method according to claim 1, characterized in that: The first solvent is one or more of N-methylpyrrolidone, water, or ethanol; the stirring time is 1-4h; The specific operation of removing impurities is: putting red phosphorus into water for ultrasonic dispersion to obtain a red phosphorus suspension, subjecting it to hydrothermal reaction, natural cooling, washing, centrifugation, and vacuum drying; the concentration of the red phosphorus suspension is 0.08 g / mL, the hydrothermal reaction temperature is 180-200° C., and then vacuum drying is performed at 65° C. for 12-24 hours.
6. The preparation method according to claim 1, characterized in that: The specific operation of ultrasonic stripping is: the red phosphorus after impurity removal is ultrasonically dispersed in a second solvent, then washed with ethanol, centrifuged, and vacuum dried; the second solvent is one or more of N-methylpyrrolidone, water, or ethanol.
7. The preparation method according to claim 5, characterized in that: The mass volume ratio of the red phosphorus after impurity removal to the second solvent is 1:1 g / L; the ultrasonic power is 800 W, and the time is 2-4 h.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The centrifugal speed is 8000-12000 rpm for 5-20 min, and then the vacuum drying is performed at 60-70° C. for 12-24 h.
9. A red phosphorus / montmorillonite light-responsive composite material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the red phosphorus / montmorillonite light-responsive composite material as claimed in claim 9 as a photocatalyst, characterized in that: Used for photocatalytic degradation of Orange II and antibacterial properties at a wavelength of 420-780nm.
Citation Information
Patent Citations
Red phosphorus / graphite phase carbon nitride composite nanosheet and preparation method and application thereof
CN108704657A
Molybdenum phosphide-red phosphorus composite photocatalyst as well as preparation method and application thereof
CN115400773A
Phosphorus-loaded biomass charcoal photocatalyst as well as preparation method and application thereof
CN118437359A
Cop2 loaded red phosphorus, preparation and use of the same
US20140069801A1
Composite photocatalyst of clay based bismuth phosphate homojunctions, preparation method and application thereof
US20240157337A1